2021
DOI: 10.1186/s43593-021-00006-8
|View full text |Cite
|
Sign up to set email alerts
|

Phonon scattering and exciton localization: molding exciton flux in two dimensional disorder energy landscape

Abstract: Two dimensional excitonic devices are of great potential to overcome the dilemma of response time and integration in current generation of electron or/and photon based systems. The ultrashort diffusion length of exciton arising from ultrafast relaxation and low carrier mobility greatly discounts the performance of excitonic devices. Phonon scattering and exciton localization are crucial to understand the modulation of exciton flux in two dimensional disorder energy landscape, which still remain elusive. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 74 publications
1
42
0
Order By: Relevance
“…From this point of view, it is necessary to gain a more comprehensive understanding on the correlation between anisotropic phonon behaviors and optical anisotropy of α-MoO 3 .Raman spectroscopy is a powerful and nondestructive characterization tool to determine the phonon dispersion near the high symmetry k-points. [18][19][20] One of the techniques is the angle-resolved polarized Raman spectroscopy, which can determine the symmetry of phonon modes and crystal orientation. [21,22] Typically, polarized Raman measurement is conducted by fixing both incident and scattered lights, while rotating the sample relative to the fixed polarized direction.…”
mentioning
confidence: 99%
“…From this point of view, it is necessary to gain a more comprehensive understanding on the correlation between anisotropic phonon behaviors and optical anisotropy of α-MoO 3 .Raman spectroscopy is a powerful and nondestructive characterization tool to determine the phonon dispersion near the high symmetry k-points. [18][19][20] One of the techniques is the angle-resolved polarized Raman spectroscopy, which can determine the symmetry of phonon modes and crystal orientation. [21,22] Typically, polarized Raman measurement is conducted by fixing both incident and scattered lights, while rotating the sample relative to the fixed polarized direction.…”
mentioning
confidence: 99%
“…Some electrons transition to triplet states through the ISC process, and the electrons thus separate according to the Pauli Exclusion Principle 45 . The electrons that are closer together have larger repulsive energy; thus, the lowest singlet states ( S 1 ) have higher energies compared with the lowest triplet states ( T 1 ) 46 , 47 . The electrons in S 1 and T 1 return to the ground state ( S 0 ) within 6.4 ns and 15.8 ms, releasing UV photons.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained DP values monotonically increased with decreasing temperature. This phenomenon can be attributed to the suppressed Elliott− Yafet spin-flip mechanism at low temperatures, [24,42] that is, the spin-flip process is generally suppressed as the temperature decreases owing to the weakened phonon scattering for spin-flip, which results in the observed higher spin polarization at lower temperatures. The highest DP was calculated to be 58.5% at 80 K, which was 2.5 times higher than that at 300 K. In addition, we found that the trend of DP with temperature at low concentration is consistent with that of Co 2+doped perovskite with Co/Pb ratio of 37% (Figure S8, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%